The Factors That Influence Dietary Habits Among International Students in the United States - Alakaam, Amir A.; Castellanos, Diana C.; Bodzio, Jessica; Harrison, Lee (Journal of International Students, 2015)
This study examines the dietary intake changes and factors related to dietary acculturation in international students attending an urban university in the United States. The researchers administered seven focus groups of college-age international students (n = 32) between June and August 2012. The participants were enrolled in Northeastern and Midwestern U.S. universities. A qualitative research inquiry was used for data collection, presentation, and analysis. An interview guide was developed to explore the dietary habits of international students. The results show the participants face many dietary challenges as a result of adapting to American culture. The major dietary-related influences include: the food environment, campus environment, religion, and individual preferences. Additionally, the consequences of dietary changes were associated with undesirable health outcomes including weight gain, increased blood glucose levels, increased cholesterol levels, high blood pressure, and mental problems.